Ekplorasi Pelaku Bullying di Pesantren - Retnowuni, Arifa; yani, athi linda (Borobudur Nursing Review, 2022)
Bullying is a behavior that is carried out intentionally with the aim of hurting the target (victim) and the action is carried out repeatedly at school or anywhere. In the past, cases of bullying in Islamic boarding schools were still common and even increasing. Such as the case of bullying which led to a beating by a student at one of the Islamic boarding schools until the death of a student who became a victim of bullying. So based on the above background, the researcher aims to explore the experience of the perpetrators in carrying out bullying actions while at the pesantren. The study wanted to explore the experiences of students who were bullies in Islamic boarding schools by using a qualitative descriptive phenomenological design, namely exploring directly, analyzing, and describing the phenomena that were studied to the fullest. Participants in the study were students who became perpetrators of bullying in Islamic boarding schools. Snowball sampling is a data source sampling technique. Information is obtained from the student coach. The research instrument is the researcher himself. The researcher as an instrument, the researcher collects the data himself through documentation, behavioral observation or in-depth interviews with the participants. Data analysis in qualitative research using the Colaizzi model. The location of the research was carried out in a dormitory in one of the Islamic boarding schools in Jombang. This study conducted interviews with 5 participants which resulted in four themes including: 1) mentally weakened, 2) tortured, 3) gained power, 4) inner satisfaction.